CHORIONIC VILLI OF THE PLACENTA: MORPHOMETRIC MATURITY PARAMETERS IN PRETERM BIRTHS - Tokar , Petro (Collection of scientific papers «ΛΌГOΣ», 2024)
Morphometric studies of chorionic villi in the placenta provide essential insights into the structural and functional changes that may contribute to the occurrence of preterm birth [1,2]. Such studies are crucial for understanding the pathogenesis of preterm labor and its implications for both the fetus and the mother [3]. Chorionic villi are key components of the placenta responsible for the exchange between maternal and fetal blood, and their morphology can reflect functional disturbances within the placenta [4].